Hydrogeochemistry and Groundwater Quality Assessment in the High Agri Valley (Southern Italy). (25th June 2021) - Paternoster, M.; Buccione, R.; Canora, F.; Buttitta, D.; Panebianco, S.; Rizzo, G.; Sinisi, R.; Summa, V.; Mongelli, G.
Abstract : The High Agri Valley (southern Italy) is one of the largest intermontane basin of the southern Apennines affected by intensive agricultural and industrial activities. The study of groundwater chemical features provides much important information useful in water resource management. In this study, hydrogeochemical investigations coupled with multivariate statistics, saturation indices, and stable isotope composition ( δ D and δ 18 O) were conducted in the High Agri Valley to determine the chemical composition of groundwater and to define the geogenic and anthropogenic influences on groundwater quality. Twenty-four sampling point ( including well and spring waters) have been examined. The isotopic data revealed that groundwater has a meteoric origin. Well waters, located on recent alluvial-lacustrine deposits in shallow porous aquifers at the valley floor, are influenced by seasonal rainfall events and show shallow circuits; conversely, spring waters from fissured and/or karstified aquifers are probably associated to deeper and longer hydrogeological circuits. The R -mode factor analysis shows that three factors explain 94% of the total variance, and F1 represents the combined effect of dolomite and silicate dissolution to explain most water chemistry. In addition, very low contents of trace elements were detected, and their distribution was principally related to natural input. Only two well waters, used for irrigation use, show critical issue for NO3 - concentrations, whose values are linked to agricultural activities. Groundwater quality strongly affects the management of water resources, as well as their suitability for domestic, agricultural, and industrial uses. Overall, our results were considered fulfilling the requirements for the inorganic component of the Water Framework Directive and Italian legislation for drinking purposes. The water quality for irrigation is from "good to permissible" to "excellent to good" although salinity and relatively high content of Mg 2+ can occasionally be critical.